Nomád - Schneiberková, Marcela (Vysoké učení technické v Brně. Fakulta výtvarných umění)
Hledání vizuální identity projektu Škola 21, pražské vzdělávací a seberozvojové iniciativy. Práce analyzuje vizi projektu a navrhuje způsoby vizuální komunikace.

Searching for the visual identity of the School 21, Prague Educational and Self-Development Initiative. The thesis analyzes the vision of the project and suggests ways of visual communication.
Nomad
Keywords: Škola 21; identita; spolek; vzdělávací iniciativa; seberozvoj; partnerství; barter; School 21; identity; association; educational initiative; self-development; partnership; barter